(untitled) (Comparatismi, 2025)
This article starts from the definition of the “personal essay” as the literary genre utilized by US feminist academics from the 1990s to claim their right not only to self-representation but also to the production of epistemologies and theory drawing from their own personal experiences. Black feminists and feminists of color have deployed this genre to denounce the history of racism in the United States and the legacy of such history in the present. In this article, I coin the definition “feminist antiracist personal essay” to identify a genre that, starting from the personal essay in the United States, has spread also in Europe, and is deployed by feminist intellectuals and activists to develop an intersectional perspective and denounce structural racism in contemporary societies and feminist movements. Through the case studies taken from the British and the Italian context, Reni Eddo-Lodge’s Why I’m No Longer Talking to White People about Race (2017) and Nadeesha Uyangoda’s L’unica persona nera nella stanza (2021), this article scrutinizes the contribution given to race studies by European Black feminists and feminists of color through the genre of the feminist antiracist personal essay.